Anticancer Activity of Aqueous Extracts from Asparagus officinalis L. Byproduct on Breast Cancer Cells - Arianna Romani (MDPI AG, 2021)
Cultivation of asparagus (Asparagus officinalis L.; Asp) for food and medicinal use has taken place since the early Roman Empire. Today, Asp represents a worldwide diffuse perennial crop. Lower portions of the spears represent a food industry waste product that can be used to extract bioactive molecules. In this study, aqueous extracts derived from the non-edible portion of the plant (hard stem) were prepared and characterized for chemical content. Furthermore, the biocompatibility and bioactivity of Asp aqueous extracts were assessed in vitro on normal fibroblasts and on breast cancer cell lines. Results showed no interference with fibroblast viability, while a remarkable cytostatic concentration-dependent activity, with significant G1/S cell cycle arrest, was specifically observed in breast cancer cells without apoptosis induction. Asp extracts were also shown to significantly inhibit cell migration. Further analyses showed that Asp extracts were characterized by specific pro-oxidant activity against tumoral cells, and, importantly, that their combination with menadione resulted in a significant enhancement of oxidants production with respect to menadione alone in breast cancer cells but not in normal cells. This selectivity of action on tumoral cells, together with the easiness of their preparation, makes the aqueous Asp extracts very attractive for further investigation in breast cancer research, particularly to investigate their role as possible co-adjuvant agents of clinical drug therapies.